2018
DOI: 10.3389/fneur.2018.01004
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Tumor and Tumor Associated Epilepsy on Subcortical Brain Structures and Long Distance Connectivity in Patients With Low Grade Glioma

Abstract: Low grade gliomas in cerebral cortex often cause symptoms related to higher cerebral functions such as attention, memory and executive function before treatment is initiated. Interestingly, focal tumors residing in one cortical region can lead to a diverse range of symptoms, indicating that the impact of a tumor is extended to multiple brain regions. We hypothesize that the presence of focal glioma in the cerebral cortex leads to alterations of distant subcortical areas and essential white matter tracts. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
4
16
0
1
Order By: Relevance
“…Indeed, structural changes in the regions distant from brain tumor have also been confirmed by some studies (Almairac et al, ; Bouwen et al, ). These structural changes have been correlated with cognition decline (Bouwen et al, ), though cognitive functions are not always caused by the alternation in the brain, sometimes the cognitive function recovers over time (Voytek et al, ), which may be attributed to the brain plasticity. Therefore, by exploring the structural alterations contributing to the integrity of cognitive function, may help to improve the preoperative plan and may result in the development of more rational strategie7s to facilitate neurorehabilitation of patients with glioma.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Indeed, structural changes in the regions distant from brain tumor have also been confirmed by some studies (Almairac et al, ; Bouwen et al, ). These structural changes have been correlated with cognition decline (Bouwen et al, ), though cognitive functions are not always caused by the alternation in the brain, sometimes the cognitive function recovers over time (Voytek et al, ), which may be attributed to the brain plasticity. Therefore, by exploring the structural alterations contributing to the integrity of cognitive function, may help to improve the preoperative plan and may result in the development of more rational strategie7s to facilitate neurorehabilitation of patients with glioma.…”
Section: Introductionmentioning
confidence: 52%
“…Some studies have suggested that localized tumors can affect the function of distant part of the brain (Liu et al, 2019;Park, Kim, Kim, Kim, & Shim, 2015;Zhang et al, 2016). Indeed, structural changes in the regions distant from brain tumor have also been confirmed by some studies (Almairac et al, 2018;Bouwen et al, 2018). These structural changes have been correlated with cognition decline (Bouwen et al, 2018), though cognitive functions are not always caused by the alternation in the brain, sometimes the cognitive function recovers over time (Voytek et al, 2010), which may be attributed to the brain plasticity.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations